A Low-Cost Programmable Logic Control (PLC) Trainer for Use in a University Agricultural Electricity Course - Dickenson, Aarron; Johnson, Donald M. (Journal of Agricultural Systems, Technology, and Management, 2006)
Programmable logic controllers (PLCs) are widely used in agricultural production and processing. Thus, agricultural systems management students should receive hands-on experience with these devices as part of their undergraduate education. However, in many cases, the cost of providing class-quantity PLCs for student laboratory use is prohibitive. This article describes a low-cost PLC trainer developed for use in a university level agricultural electricity course. A sample laboratory activity used with the PLC trainer is also described. End-of-course student comments indicated that use of the trainer had stimulated student interest in learning more about programmable logic controllers.